2008
DOI: 10.1002/chem.200800547
|View full text |Cite
|
Sign up to set email alerts
|

Microsolvation Effects on the Optical Properties of Crystal Violet

Abstract: We present a joint experimental and theoretical study of the photoabsorption and photodissociation behavior of crystal violet, that is, the tris[p-(dimethylamino)phenyl]methyl cation. The photodissociation spectra of isolated and microsolvated crystal violet have been measured. A single band is observed for the bare cation. This is in good agreement with the calculated vibronic absorption spectrum based on time-dependent density functional theory calculations. The interaction of crystal violet with a single wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
21
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 45 publications
7
21
0
Order By: Relevance
“…We find that the image field effects are comparable to those due to solvation and are in good agreement with the experimental absorption spectra in solution where the two states are found at 587 and 539 nm, respectively. 48 We also find that the excitation energies depend strongly on the orientation of the molecule near the metal surface. Orientations where the transition dipole moment is aligned with the edge of the nanoparticle lead to shifts of up to 15 nm.…”
Section: Moleculeàmetal Interactions Within the Dim/qm Methodsmentioning
confidence: 95%
“…We find that the image field effects are comparable to those due to solvation and are in good agreement with the experimental absorption spectra in solution where the two states are found at 587 and 539 nm, respectively. 48 We also find that the excitation energies depend strongly on the orientation of the molecule near the metal surface. Orientations where the transition dipole moment is aligned with the edge of the nanoparticle lead to shifts of up to 15 nm.…”
Section: Moleculeàmetal Interactions Within the Dim/qm Methodsmentioning
confidence: 95%
“…These UV-VIS results for [RA] 2support the previous hypothesis of solvent specific interaction used to justify the presence of the higher-energy shoulder observed in CV absorption spectrum. 14,26 Aiming to better support such assumptions, a resonance Raman investigation was done.…”
Section: Resultsmentioning
confidence: 99%
“…In the same paper Kahr et al showed that Raman spectroscopy was unable to distinguish between to CV hydrates in different crystalline symmetry groups. 22 More recently Loison et al 26 showed that the shoulder is due to interactions of CV with its environment, by presenting the photodissociation spectra for isolated CV and CV-H 2 O complex without and with a shoulder, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with previous gas phase measurements of rhodamine derivatives, where similar profiles to those observed in solution are also found, and indeed with other poly-aromatic dyes, indicating this may be a more general phenomenon. 20,22,23,35,36 Additionally, gas-phase action spectroscopy performed upon pseudo-dimers of rhodamine 575, where the dimerization is created by enforced proximity of the dyes following grafting onto a tri-peptide, shows there is only a small shift in the position of the absorption maximum relative to the monomeric species. 31 Moreover, recent solution phase measurements of pyronin B dimers in solution found their absorption and fluorescence properties to differ only very slightly from the monomer.…”
Section: Resultsmentioning
confidence: 99%